Near‐silent distortionless DWI using magnetization‐prepared RUFIS. Issue 1 (29th November 2019) - Yuan, Jianmin; Hu, Yuxin; Menini, Anne; Sandino, Christopher M.; Sandberg, Jesse; Sheth, Vipul; Moran, Catherine J.; Alley, Marcus; Lustig, Michael; Hargreaves, Brian; Vasanawala, Shreyas
Abstract : Purpose: To develop a near‐silent and distortionless DWI (sd‐DWI) sequence using magnetization‐prepared rotating ultrafast imaging sequence. Methods: A rotating ultrafast imaging sequence was modified with driven‐equilibrium diffusion preparation, including eddy‐current compensation methods. To compensate for the T1 recovery during readout, a phase‐cycling method was used. Both compensation methods were validated in phantoms. The optimized sequence was compared with an EPI diffusion sequence for image distortion, contrast, ADC, and acoustic noise level in phantoms. The sequence was evaluated in 1 brain volunteer, 5 prostate volunteers, and 10 pediatric patients with joint diseases. Results: Combination of several eddy‐current compensation methods reduced the artifact to an acceptable level. Phase cycling reduced T1 recovery contamination during readout. In phantom scans, the optimized sequence generated similar image contrast to the EPI diffusion sequence, and ADC maps between the sequences were comparable; sd‐DWI had significantly lower acoustic noise ( P < .05). In vivo brain scan showed reduced image distortion in sd‐DWI compared with the EPI diffusion, although residual motion artifact remains due to brain pulsation. The prostate scans showed that sd‐DWI can provide similar ADC compared with EPI diffusion, with no image distortion. Patient scans showed that the sequence can clearly depict joint lesions. Conclusion: An sd‐DWI sequence was developed and optimized. Compared with conventional EPI diffusion, sd‐DWI provided similar diffusion contrast, accurate ADC measurement, improved image quality, and minimal ambient scanning noise. The sequence showed the ability to obtain in vivo diffusion contrast in relatively motion‐free body regions, such as prostate and joint.